2011
DOI: 10.1177/0038038511416149
|View full text |Cite
|
Sign up to set email alerts
|

Off the Leash and Out of Control: Masculinities and Embodiment in Eastern European Stag Tourism

Abstract: Sociology 45(6) 977 -991 AbstractEntrenched conceptions of masculinity have constructed the male body as bounded and controlled. This article discusses the centrality of a particular construction of the male body to the phenomenon of British premarital stag party tourism to Eastern European cities. Drawing on data from participant-observation in Kraków, Poland, it is shown that the tour participants enact an embodied masculinity which is unruly and unrestrained. The stag tour experience is embodied through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 16 publications
0
51
0
1
Order By: Relevance
“…In Western countries, where alcohol is permissible by law and tradition, and a part of popular culture, the consumption of alcohol plays a crucial role in the social construction of gender (Lyons and Willott, 2008;Thurnell-Read, 2011). Historically, drinking in bars was viewed as acceptable for men and unacceptable for 'decent' women.…”
Section: Drinking Leisure and Communitymentioning
confidence: 99%
“…In Western countries, where alcohol is permissible by law and tradition, and a part of popular culture, the consumption of alcohol plays a crucial role in the social construction of gender (Lyons and Willott, 2008;Thurnell-Read, 2011). Historically, drinking in bars was viewed as acceptable for men and unacceptable for 'decent' women.…”
Section: Drinking Leisure and Communitymentioning
confidence: 99%
“…The consumption of alcohol and development of masculine identities has been discussed extensively in literature since the latter half of the twentieth century (see Jayne, Gibson, Waitt and Valentine, 2012;Leyshon, 2008;Jayne, Valentine and Holloway, 2008a, 2008bPeralta, 2007;Thurnell-Read, 2011;Valentine, Jayne and Holloway, 2010;Waitt, Markwell and Gorman-Murray, 2008;Waitt, Jesop and Gorman-Murray, 2011). …”
Section: Gender Drinking and Performancementioning
confidence: 99%
“…In the lead author's experience at working at other real-ale festivals, this is typical, though in his experience there are more younger men ordering full pints, especially on the final nights of the festivals when they attract more of a passing 'outin-town' crowd of young male drinkers. Men, especially working-class men, still face social and psychological pressure to drink pints, not halves -halves are seen as effeminate, weak, and unbecoming of heterosexual, hegemonic masculinity (Jayne, Valentine and Holloway, 2011;Thurnell-Read, 2011). The real-ale tourists however, need to balance their displays of Butlerian heteronormativity (Butler, 2006) with the need to sample as diverse a range of beers as possible, while being sober enough to stand up (to prove one's ability to take one's drink): as Hamish explained, trying to prove his own masculinity to the second author of this paper, the aim is 'tasting new beers not tasted before… do try to keep track, but by end of night to be honest I've lost count'.…”
Section: Later In the Afternoon I Bumped Into Ecks When I Was Headingmentioning
confidence: 99%
“…Therefore, campaigns that target individual harms arising from HED may be dismissed as irrelevant, particularly given that many are perceived to employ a patronizing, paternalistic, or preaching tone (de Visser et al, 2013). Peer group drinking and drunkenness are important aspects of the social lives of many young people: the individual experience of intoxication is often accompanied by enhanced feelings of togetherness (Brown & Gregg, 2012;de Visser et al, 2013;Fry, 2011;Jayne et al, 2010;Livingstone, Young & Manstead, 2011;MacNeela & Bredin, 2011;Szmigin et al, 2011;Thurnell-Read, 2011). Furthermore, recent qualitative research has revealed that many young people believe that some negative aspects of drinking -such as caring for drunk friends, being cared for when drunk, and suffering through hangovers with friends -offer opportunities for strengthening interpersonal bonds (de Visser et al, 2013).…”
Section: Young People and Alcoholmentioning
confidence: 99%